2011
DOI: 10.1175/mwr-d-10-05036.1
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Storm Longevity on the Pattern of Deep Convection Initiation in a Low-Shear Environment

Abstract: The sensitivity of storm longevity to the pattern of deep convection initiation (e.g., multiple, quasi-linearly arranged initial deep convective cells versus an isolated deep convective cell) is examined using idealized cloud-resolving simulations conducted with a low-shear initial environment. When multiple deep convective cells are initialized in close proximity to one another using either a line of thermals or a shallow airmass boundary, long-lived storms are produced. However, when isolated deep convection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 35 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Most popular is the idea that convergence at the gust front organizes upward motion on larger scales than that of normal turbulence, thus creating larger air parcels that entrain less (Kuang and Bretherton 2006;Khairoutdinov and Randall 2006). Others suggest that enhanced lifting due to convergence at the gust front is the key process, either because it helps parcels reach the level of free convection (Grandpeix and Lafore 2010;Houston and Wilhelmson 2011) or because it weakens entrainment by reducing the time spent per unit distance over which the parcels rise (Del Genio and FlG. 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most popular is the idea that convergence at the gust front organizes upward motion on larger scales than that of normal turbulence, thus creating larger air parcels that entrain less (Kuang and Bretherton 2006;Khairoutdinov and Randall 2006). Others suggest that enhanced lifting due to convergence at the gust front is the key process, either because it helps parcels reach the level of free convection (Grandpeix and Lafore 2010;Houston and Wilhelmson 2011) or because it weakens entrainment by reducing the time spent per unit distance over which the parcels rise (Del Genio and FlG. 15.…”
Section: Discussionmentioning
confidence: 99%
“…Convective available potential energy from the Xie et al (2010) data was moderate (1647 and 2273 J kg~^ for the active and break periods, respectively), and the cold pool temperature perturbation was ~4 K (see section 3), putting the atmosphere well within the weak shear regime whether this is assessed using a full troposphere convective Richardson number (Tao and Moncrieff 2009) or a local index of low-level buoyant vorticity generation relative to shear at the gust front (Rotunno et al 1988). Houston and Wilhelmson (2011) have shown that organized, long-lived convection can occur in low shear conditions as long as a sufficiently deep cold pool is produced.…”
Section: B Simulation Designmentioning
confidence: 99%
“…Schumacher and Johnson () examined the organization and environmental properties of extreme‐rain‐producing MCSs in the United States over a 3‐year period and showed that extreme local rainfall is often associated with back‐building/quasi‐stationary MCSs, which occur when new convective cells repeatedly form upstream of their predecessors and pass over a particular area. The continuous development of upstream convection requires triggering factors, for example, frontal lifting (Schumacher et al, ), outflow boundaries (Houston & Wilhelmson, ; Houze, ; Jeong et al, ; Schumacher, ; Schumacher & Peters, ; Wang et al, ), interaction between the low‐level jet and the midlevel circulation (mesoscale convective vortices; Schumacher, ; Schumacher & Johnson, , ), orographic lifting (Duffourg et al, ; Soderholm et al, ), and thermodynamic effects associated with latent heating/cooling (Wang et al, ). Schumacher and Johnson () also indicated that back‐building/quasi‐stationary MCSs are more dependent on mesoscale and storm‐scale processes, particularly lifting provided by cold outflows from previous convection, than on preexisting synoptic boundaries.…”
Section: Analysis Of Key Factors For the Heavy Rainfallmentioning
confidence: 99%
“…While the importance of vertical wind shear in organizing quasi-linear convective systems has been well documented in the literature (e.g., Thorpe et al 1982;Rotunno et al 1988;Parker and Johnson 2000;Weisman and Rotunno 2004;Cohen et al 2007), the role of lowlevel shear verses deep-layer shear, as well as the physical interpretation of their significance is still being investigated (e.g., Houston and Wilhelmson 2011;Coniglio et al 2012). For the decaying and slowly decaying events explored in this study, the mean low-level shear (0-3 km) declines ;1.4 and ;0.7 m s 21 , respectively, between T 2 3 h and T 2 0 h, though it increases by 4.7 m s 21 for sustaining coastal linear convection (Figs.…”
Section: Discussionmentioning
confidence: 99%